Botulinum Toxin in Gynaecology - Gray, Thomas; Jha, Swati (Current Women's Health Reviews, 2016)
Background: The use of botulinum toxin for gynaecological indications is becoming increasingly established for women whose conditions remain refractory to conventional treatment. In this review we assessed the current available literature detailing the use of botulinum toxin to treat detrusor overactivity, painful bladder syndrome, vaginismus, localized vulvodynia and chronic pelvic pain. Methods: A review of literature was undertaken using the key words “botulinum toxin”, “vaginismus”, “vulvodynia”, “vulval vestibulitis”, “detrusor overactivity”, “overactive bladder”, “interstitial cystitis”, “painful bladder syndrome” and “chronic pelvic pain”. All relevant publications between 1985 and 2016 form the basis of this review. Results: The only licenced use of botulinum toxin is detrusor overactivity. Other uses include vaginismus, painful bladder syndrome, chronic pelvic pain and localized vulvodynia where there is some evidence for its use. The best evidence available is for detrusor overactivity where multiple randomised trials and two systematic reviews have been published. Further research is needed to determine long-term outcomes and the most effective regime for using botulinum toxin for detrusor overactivity. Three randomised controlled trials and multiple prospective non-randomised studies have been published regarding the use of botulinum toxin for painful bladder syndrome. This seems an effective treatment, but further research is needed. Evidence for the use of botulinum toxin for vaginismus, localized vulvodynia and chronic pelvic pain is based largely on case series and non-randomised prospective studies. Conclusion: An increasing body of evidence is emerging for the use of botulinum toxin for patients refractory to conventional treatment in these areas. Further good quality research is needed.
Keywords: Botulinum toxin